Factors Determining Risk Tolerance of Individual Investors in Kathmandu Valley - Neupane, Prabriti (Journal of Business and Social Sciences Research, 2021)
The paper aims to evaluate the various factors influencing the risk tolerance of individual investors in Kathmandu Valley. Seven factors which are: time horizon, investment preference, financial knowledge, investment objective, personality traits, herd behaviour, and consultancy effect, and overconfidence are used. The study used a descriptive research design and collected primary data through structured questionnaires to conduct quantitative analysis. Using a convenience sampling method, responses from 200 individual investors residing in the Kathmandu Valley were collected. The research used descriptive statistics and regression to measure the variables having a significant impact on the risk tolerance level. It was found that amongst the variables, time horizon, herd behaviour and consultancy effect, and overconfidence have a positive significant impact on risk tolerance.